2022
DOI: 10.1186/s12879-022-07410-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antimicrobial stewardship programs on antibiotic consumption and antimicrobial resistance in four Colombian healthcare institutions

Abstract: Background Antimicrobial stewardship programs (ASPs) have become a fundamental pillar in optimizing antimicrobial usage, improving patient care, and reducing antimicrobial resistance (AMR). Herein we evaluated the impact of an ASP on antimicrobial consumption and AMR in Colombia. Methods We designed a retrospective observational study and measured trends in antibiotic consumption and AMR before and after the implementation of an ASP using interrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…The DTC organized Committee members and clinical medicine and clinical pharmacy experts to conduct dynamic monitoring of prescribed medications, regularly sampling prescriptions or cases for reasonable evaluation. The evaluation results have been reported ( Yang et al, 2021 ; Pallares et al, 2022 ). The types of irrational drug use, DTC interventions, and outcomes of the intervention were recorded by clinical pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…The DTC organized Committee members and clinical medicine and clinical pharmacy experts to conduct dynamic monitoring of prescribed medications, regularly sampling prescriptions or cases for reasonable evaluation. The evaluation results have been reported ( Yang et al, 2021 ; Pallares et al, 2022 ). The types of irrational drug use, DTC interventions, and outcomes of the intervention were recorded by clinical pharmacists.…”
Section: Methodsmentioning
confidence: 99%
“…ASPs brought about positive clinical outcomes in hospital inpatients in most cases. Microbiological outcomes to assess the impact of ASP were reported in 42% (22/53) of studies [ 63 , 65 , 66 , 71 , 76 , 79 , 81 85 , 87 89 , 100 , 101 , 109 , 110 ], including a decrease in the prevalence of multi-drug resistance bacterial strains like Acinetobacter spp , Methicillin-Resistant Staphylococcus aureus (MRSA) , Vancomycin-Resistant Enterococcus [VRE], increase in the antibiotic susceptibility of bacterial strains such as Pseudomonas aeruginosa, E. coli [ 71 , 81 , 82 , 85 ]. Studies also documented a reduction in the incidence of bacterial infections such as Clostridioides difficile infections and Candidemia [ 75 , 77 ], and a decrease in pan-drug resistant isolates [ 65 , 71 , 77 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our review found that ASP interventions achieved improvement in rational antibiotic prescription through dose optimization, antibiotic de-escalation, and a reduction in antibiotic prescriptions. ASP implementation documented a reduction in the consumption of WATCH category antibiotics such as vancomycin, meropenem, aztreonam, ceftriaxone, and RESERVE category antimicrobials like colistin, carbapenems, teicoplanin, in hospital wards and ICUs [ 46 , 63 , 71 , 77 , 82 , 83 , 100 102 ]. Prior systematic reviews demonstrated a decrease in antibiotic consumption after ASP implementation in the ICUs of hospitals [ 2 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all these situations, intensivists should be more attentive to guidelines. By reducing inappropriate prescriptions, antibiotic consumption and drug resistance [43,44], the ASP has provided strong evidence of e cacy, but they are time-consuming and require dedicated funding. We suggest a daily ASP in these error-prone situations, to improve compliance with guidelines.…”
Section: Discussionmentioning
confidence: 99%